Memória coletiva e suas representações: estudo da literatura em suas relações com a sociedade no ensino médio - Marques, Gêlda Karla da Silva (2016)
This research is about a study on the discussion of relevant issues related to the teaching of literature as well as to the construction and application of a didactic sequence directed to High School. In this way, there are the proposal and the deployment of an experience of research/teaching/learning developed with High School students from the Federal Institution of Education, Science and Technology – Campus Princesa Isabel – Paraíba – Brazil. Its main aim is to construct an the notion of collective memory intending the development of the literary reading and the appreciation of the material/immaterial heritage in High School classes in that city where the appreciation of the experience, the past and wisdom have been losing their importance in the information era. Through semistructured interviews, questionnaire applications and experience reports on the literature classes there is the literature teaching with the historical and cultural heritage of the students. This research is based on the desire to provoke changes in the literature teaching since there is the link between the literary text to the conceptions of the world and the life of a community, joining a pedagogical project to the new technologies which make part of the student day-by-day.